2015
DOI: 10.2527/jas.2015-9139
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus digestibility and phytate degradation by yearlings and mature horses1,2

Abstract: Inorganic P is often added to growing horse diets because organic P, or phytate-P, is believed to have lower digestibility. If horses can efficiently digest organic P, then the need for inorganic P may be reduced. Much of the P in grain-based concentrates fed to growing horses is in the form of phytate-P. Little is known about the ability of growing horses to degrade phytate-P or whether horse age affects mineral digestion in horses. The objective of this study was to examine the effect of age on P, Ca, and Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
6
12
1
Order By: Relevance
“…The excretion of phosphorus observed here was within the ranges presented in the literature [7,12,18,33,34]. P excretion is linearly related to its intake, and the intake increases with the increasing concentrate ingestion [10,12,33].…”
Section: Intake Fecal Excretion and Digestibility Of Phosphorussupporting
confidence: 79%
See 3 more Smart Citations
“…The excretion of phosphorus observed here was within the ranges presented in the literature [7,12,18,33,34]. P excretion is linearly related to its intake, and the intake increases with the increasing concentrate ingestion [10,12,33].…”
Section: Intake Fecal Excretion and Digestibility Of Phosphorussupporting
confidence: 79%
“…There may be some improvement in phosphorus absorption as the need for phosphorus increases, for example, through exercise or when the phosphorus content of the diet increases [6]. Fowler et al [7] concluded that yearlings can utilize organic P as well as mature horses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of nutrients excreted by the horse in dung and urine depend highly on the nutrition and feed quality (Graham-Thiers and Bowen 2011, Ögren 2013, Ögren et al 2014, Fowler et al 2015, Trottier et al 2016, optimization of which is an important tool in reducing excess nutrient load from horse operations. Averages of around 500 horse manure samples analyzed in Finland in a commercial laboratory, Eurofins Viljavuuspalvelu Oy, between 2005 and 2009 were 15 g kg -1 dw for total N, 3 g kg -1…”
Section: Discussionmentioning
confidence: 99%